EPR Study of Paramagnetic Centers in Human Blood - Kubiak, Tomasz; Krzyminiewski, Ryszard; Dobosz, Bernadeta (Current Topics in Biophysics, 2013)
Electron paramagnetic resonance investigations of paramagnetic centers in whole human blood were carried out at 170 K using X-band EPR spectrometer. The study included a group of patients and healthy volunteers. The EPR signals from high spin Fe3+ ions in transferrin (g = 4.2) and Cu2+ ions in ceruloplasmin (g = 2.05) are characteristic of each frozen blood sample. An overview of all recorded spectra revealed in several cases additional lines derived from high spin Fe3+ ions in methemoglobin (g = 5.8 - 6), free radicals (g = 2.002 - 2.005) and various low spin ferriheme complexes (g = 2.21 - 2.91). The lines from cytochromes (g = 3.03 and 3.27) were observed only twice. The EPR measurements have not confirmed the correlation between the occurrence of a particular type of low-spin iron complex and a specific disease entity. Moreover, the presence of EPR lines from trivalent iron also did not differentiate patients from healthy volunteers.